The natural anti-tumor compound Celastrol targets a Myb-C/EBPβ-p300 transcriptional module implicated in myeloid gene expression - Coulibaly, Anna (PLOS ONE, 2018)
Myb is a key regulator of hematopoietic progenitor cell proliferation and differentiation and has emerged as a potential target for the treatment of acute leukemia. Using a myeloid cell line with a stably integrated Myb-inducible reporter gene as a screening tool we have previously identified Celastrol, a natural compound with anti-tumor activity, as a potent Myb inhibitor that disrupts the interaction of Myb with the co-activator p300. We showed that Celastrol inhibits the proliferation of acute myeloid leukemia (AML) cells and prolongs the survival of mice in an in vivo model of AML, demonstrating that targeting Myb with a small-molecule inhibitor is feasible and might have potential as a therapeutic approach against AML. Recently we became aware that the reporter system used for Myb inhibitor screening also responds to inhibition of C/EBPβ, a transcription factor known to cooperate with Myb in myeloid cells. By re-investigating the inhibitory potential of Celastrol we have found that Celastrol also strongly inhibits the activity of C/EBPβ by disrupting its interaction with the Taz2 domain of p300. Together with previous studies our work reveals that Celastrol independently targets Myb and C/EBPβ by disrupting the interaction of both transcription factors with p300. Myb, C/EBPβ and p300 cooperate in myeloid-specific gene expression and, as shown recently, are associated with so-called super-enhancers in AML cells that have been implicated in the maintenance of the leukemia. We hypothesize that the ability of Celastrol to disrupt the activity of a transcriptional Myb-C/EBPβ-p300 module might explain its promising anti-leukemic activity.
Gesehen am 04.10.2019